Rotating biological contactors of the future for enhanced ammonium removal. - Freeman, Daniel (Cranfield University, 2016)
Rotating biological contactors (RBCs) are competitive wastewater treatment technologies for small wastewater treatment works (WWTs) due to their low energy, low maintenance and capacity for ammonium removal. Due to stricter environmental quality standards (EQS) as well as increased pressure on companies to cut cost and decrease energy consumption, RBC performance must be optimised to maintain competitiveness in the future. Optimisation can be achieved by altering operational parameters to yield a more conducive environment for ammonia oxidising microorganisms (AOM) to proliferate and increase their metabolic activity. The effects of altering these operational parameters was assessed using data from a range of sources, including fully operational WWTs. For instance, 2 fully operational WWTs were employed to test the effect of rotational speed, results indicated that increasing the speed from 1 rotation per minute (rpm) to 1.3 rpm enhanced the capacity for ammonium load removal. The effect of artificial aeration in another fully operational overloaded RBC led to significant improvement in ammonium load removal (46 %). Both routes to optimisation resulted in a thinner biofilm with less Beggiatoa (filamentous bacteria) present. It was concluded that retrofitting RBCs to implement these optimisation methods can be achieved with little expenditure, of approximately £10 000 life cycle cost. A novel performance robustness tool was used to identify any additional factors that significantly contributed to performance enhancement across a very large number (121) of fully operational WWTs, however no correlation could be found. High throughput DNA sequencing and quantitative PCR of RBC biofilm from 7 fully operational WWTs enabled an in depth investigation into AOM responsible for ammonium removal. Results indicated that ammonia oxidising archaea (AOA) generally dominated the biofilm, however ammonia oxidising bacteria (AOB) were more competitive when exposed to lower loading. Candidatus nitrososphaera and Nitrosomonas ureae were the dominant AOA and AOB, respectively.